ARTIFICIAL INTELLIGENCE AND EMPLOYABILITY SKILLS IN HOSPITALITY EDUCATION: EVIDENCE FROM INDIAN INSTITUTIONS - Sathiamoorthy, Rajesh; Sharma, Ankita Sakhuja (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Artificial Intelligence (AI) has brought revolutionary changes to the hospitality industry through automation and improved decision-making, and has created hybrid jobs that require competencies from both the technological and hospitality sides. The growing need for AI competence in the industry has led to the development of digital literacy among employees. However, the hospitality education system has been reluctant to integrate such aspects into its curricula, and thus, the employability readiness of hospitality students is at risk. In view of the above, the study evaluates hospitality students' employability readiness in the context of artificial intelligence integration in industry, with particular focus on technical abilities, career preparedness, and willingness to upgrade their qualifications to meet industry needs. Quantitative cross-sectional research has been implemented, using a structured questionnaire. It included 377 hospitality students who answered 46 questions regarding their technical abilities, career preparedness, and willingness to acquire additional skills. A five-level Likert scale was used for data collection. Descriptive statistics (mean and standard deviation) were used as measures of central tendency, and internal reliability was evaluated using Cronbach's Alpha (α = 0.983). It should be noted that the analysis shows that the overall level of employability readiness in the field of AI integration is relatively high, with career readiness and willingness to upgrade especially high (students are highly motivated to adapt to industry changes). However, relatively low marks in technical abilities indicate that students are not well-equipped, technologically speaking. Thus, there is a considerable gap between theoretical knowledge and students' practical skills. It can be concluded that, despite students' high adaptability and employability readiness regarding AI implementation, they lack the practical skills to operate in such conditions.